Ανάπτυξη μικρoρρoικoύ (Microfluidics) και ανάλυση της ροής αίματος σε μικρoαγωγoύς - Ασημένος, Κωνσταντίνος (My University, 2022)
We are researching a device that will use the methods we analyzed in our laboratory and will characterize the levels of inflammation and blood clotting. Our device will measure blood clotting, blood clotting time and blood inflammation through an agglomeration indicator. We try to improve the microtubule where the blood will flow which is accurate in blood measurements. The microfluidizer consists of microscope glass plates that have been surface treated to promote hydrophilicity, surface tension expansion and flow rate. Laser techniques were used in combination with cleaning protocols and the application of TiO2 to the surfaces (Titanium Dioxide). The findings revealed that the surface roughness factor affects the hydrophilicity of a material and extends the velocity of the meniscus to a microfluidic device. Finally, surface hydrophilicity and surface flow stresses in the pipeline were significantly improved, to the point that the hydrophilicity of the angle difference between the original surface and the same surface after treatment according to protocol reached in some cases up to 7.8°. The use of specialized approaches to the development of microcirculation systems has significant potential for enhancing the intensity and flow control of microfluidic devices.
Keywords: Ροή αίματος σε μικροαγωγούς